Prevention of mildly symptomatic precancerous diseases of the oral cavity, taking into account the possibility of eliminating its causative factors - Vatamanyuk N.V. (Research Retrieval and Academic Letters, 2024)
The possibility of inflammatory diseases of the teeth and changes in the mucous membrane of the oral cavity in the form of leuko- and erythroplakia, hyperkeratoses and papillomas is associated with the influence of microflora. Contributing factors include prolonged pressure from dentures, broken teeth, smoking, alcohol consumption and exposure to workplace hazards. The purpose of the study is to substantiate the possibility of oral cancer prevention, taking into account its causative factors and the effectiveness of treatment and diagnostic tactics with an evaluation of the results. The study included 34 patients with precancerous conditions of the oral cavity. According to the anamnesis, local changes were asymptomatic, painless and were detected during dental treatment. The results showed the presence of various changes such as papillomatous masses, hyperkeratoses, leukoplakias and warty leukoplakias. Histological examination confirmed the atypia of the basal cell epithelium, indicating the initial stage of malignancy. Conclusions were made about the reality of oral cavity cancer prevention, taking into account the possibility of eliminating its causative factors and the need for regular examination to detect precancerous changes